Eurobarometer 43.1: International trade and radiation protection, April-May 1995 - Reif, Karlheinz; Marlier, Eric; Commission of the European Communities (Commission of the European Communities, 1997)
This round of Eurobarometer surveys queried respondents on standard Eurobarometer measures such as public awareness of and attitudes toward the European Union (EU), and also focused on new member states, the General Agreement on Tariffs and Trade (GATT), and radiation. Questions concerning the addition of Austria, Finland, and Sweden to the EU on January 1, 1995, were asked, focusing on whether the addition of these countries would have a positive, negative, or no effect on individuals, their country, the EU, gender equality in the EU, unemployment in the EU, policy toward Eastern Europe, and worldwide competitiveness. Respondents were queried about international trade, GATT, and, in particular, their opinions regarding economic relationships between counties and how member states' interests should be represented and protected internationally. Radiation questions covered information sources regarding exposure risks and radioactivity levels, satisfaction with information sources, and opinions about radioactivity and exposure risks. Demographic and other background information was gathered on number of people residing in the home, size of locality, region of residence, and occupation of the head of household, as well as the respondent's age, sex, marital status, education, occupation, left-right political self-placement, and ownership of durables.

Denna omgång av Eurobarometern undersökte respondenternas inställning till typiska Eurobarometer-mått såsom allmänhetens medvetenhet om, och attityder till, Europeiska Unionen (EU). Därtill sattes fokus på nya medlemsländer, det Allmänna tull- och handelsavtalet (GATT) samt strålning. Frågor ställdes angående Österrikes, Finlands och Sveriges inträde i EU den 1 januari 1995 med fokus på om detta skulle komma att ha en positiv, negativ alternativt ingen effekt för respondenterna själva, deras land, EU, jämställdhet inom EU, arbetslöshet inom EU, politiken gentemot Östeuropa samt EU:s internationella konkurrenskraft. Frågor ställdes om internationell handel och GATT. Av särskilt intresse var respondenternas åsikter om ekonomiska relationer mellan länder och hur medlemsländernas intressen borde representeras och skyddas internationellt. Frågor om strålning täckte respondenternas informationskällor rörande exponeringsrisker och radioaktivitetsnivåer, tillfredsställelse med dessa samt åsikter om radioaktivitet och exponeringsrisker. Demografisk information samlades in gällande antalet personer i hushållet, ortsstorlek, tillhörande region och familjeförsörjarens yrke. Annan bakgrundsinformation som samlades in var respondentens ålder, kön, civilstånd, ålder vid avslutad utbildning, nuvarande och tidigare yrken, självplacering på den politiska vänster-högerskalan samt ägande av kapitalvaror.
Eurobarometer 43.1: International trade and radiation protection, April-May 1995
EB 43.1
Keywords: Environment and conservation; Miljö och naturvård; International politics and organisations; Internationell politik och organisationer; TRADE, INDUSTRY AND MARKETS; HANDEL, INDUSTRI OCH MARKNADER; Social Sciences; Samhällsvetenskap